Human Resource Management in Integrated Islamic Junior High School - Sumirah Sumirah; Jamrizal Jamrizal; Ely Surraya; Syamsul Huda; Anggi Fitri (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine how teachers can implement human resource management (HR) at the Integrated Islamic School (SIT). This study focuses on teacher human resources at a Junior High School (SMPIT) Jambi. This research is descriptive qualitative research. The data collection techniques used were observation, interviews, and documentation, while the data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results of the field research show that the implementation of teacher HR management at SMPIT Al Fatih Jambi has not been implemented perfectly, judging from the performance of the teachers and the lack of firmness of a leader or principal. Several things must be considered, especially with regard to the selection process, placement, and teacher performance.